Efeitos do ensino de tato com estímulos de alta e baixa preferência na aprendizagem de um pequeno vocabulário em segunda língua - Gonçalves, Maíra Costa (Universidade Federal de São Carlos, 2022)
There is a growing body of literature examining the effectiveness of teaching a foreign language using behavior-analytic procedures. This study compared the acquisition of foreign tact responding as a function of stimulus preference and assessed the emergence of bidirectional intraverbal responses (Native-Foreign and Foreign-Native). Three typically developing Brazilian children participated. Sessions were conducted remotely using a platform for video and audio communications. First, the experimenter conducted a preference assessment to select the target stimuli for each participant based on their level of stimuli preference (high and low-preferred stimulus sets). During tact instruction, the experimenter presented a visual stimulus and asked for its foreign name. A progressive prompt delay was used. Emergent intraverbal responses were evaluated across Native-Foreign and Foreign-Native directions before and after instruction. Results showed that all participants met the learning and the emergence criterion for the high preferred stimulus set in fewer trial blocks than for the low preferred stimulus set. Also, high-preferred set yielded greater emergence of all intraverbal relations compared to low-preferred set. Results confirmed previous studies, showing that tact instruction is effective to produce emergent intraverbal responding, and suggested the stimulus preference as an important variable to ensure optimal foreign language teaching procedures.
Effects of stimulus preference on the acquisition of a small foreign language vocabulary
Keywords: Ensino de tato; Intraverbal bidirecional; Segunda língua; Preferência dos estímulos; Respostas emergentes; Tact instruction; Bidirectional intraverbal; Second language; Stimulus preference; Emergent responding; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA EXPERIMENTAL::PROCESSOS DE APRENDIZAGEM, MEMORIA E MOTIVACAO